Respuesta :
Answer: [tex]f'(-3)=538[/tex]
Step by step:
To get the derivative you can either multiply out the product (which I did below), or apply the formula for the derivative of a product of two functions. Either way you will obtain the same result, of course.
[tex]f(x) = (2x^2-7x)(-x^2-7)=-2 x^4 + 7 x^3 - 14 x^2 + 49 x\\f'(x) = -8x^3 +21x^2 - 28x +49\\f'(-3)=538[/tex]
use product rule
[tex]\frac{d}{dx} g(x)h(x)=g'(x)h(x)+g(x)h'(x)[/tex] (where the ' symbol is derivitive with respect to x, (just using Leibniz notation)
also remember the power rule: [tex]\frac{d}{dx} x^n=nx^{n-1}[/tex]
and sum rule, [tex]\frac{d}{dx} (g(x)+h(x))=\frac{d}{dx}g(x)+\frac{d}{dx}h(x)[/tex]
so first find the derivitive then evaluate it
if we say that [tex]2x^2-7x=g(x)[/tex] and [tex]-x^2-7=h(x)[/tex]
setup:
find g'(x) and h'(x)
[tex] g'(x)=2*2x^1-7*1x^0=4x-7*1=4x-7[/tex]
[tex]h'(x)=2*(-x^1)-0=-2x[/tex]
so [tex]f'(x)=g'(x)h(x)+g(x)h'(x)=(4x-7)(-x^2-7)+(2x^2-7x)(-2x)[/tex]
evaluate f'(-3)
[tex]f'(-3)=(4(-3)-7)(-(-3)^2-7)+(2(-3)^2-7(-3))(-2(-3))[/tex]
[tex]f'(-3)=(-19)(-16)+(39)(6)[/tex]
[tex]f'(-3)=538[/tex]
answer: f'(-3)=538